2021
DOI: 10.1111/1365-2656.13493
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to vector‐based transmission in a honeybee virus

Abstract: 1. Global pollinator declines as a result of emerging infectious diseases are of major concern. Managed honeybees Apis mellifera are susceptible to numerous parasites and pathogens, many of which appear to be transmissible to sympatric non-Apis taxa. The ectoparasitic mite Varroa destructor is considered to be the most significant threat to honeybees due to its role in vectoring RNA viruses, particularly Deformed wing virus (DWV). Vector transmission of DWV has resulted in the accumulation of high viral loads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 130 publications
(169 reference statements)
4
32
0
Order By: Relevance
“…These results from experimentally manipulated honeybee colonies are in striking accordance with an independent study at the population level: studying honeybee and bumblebee populations in Varroa-free island refugia and in island and mainland sites positive for Varroa, Manley et al (2019) found that the presence of Varroa increased DWV-B prevalence and viral load both in Varroa's honeybee host as well as in wild bumblebees not infested by Varroa, but that DWV-A was virtually absent in the Varroa-free sites (Figure 1). Norton et al (2021) interpret these results as showing that DWV-B's recent increase in Europe and North America is not driven by selective pressure by the vector, which essentially suggests that DWV-B's spread is driven by higher reproductive capacity in honeybees irrespective of vector-borne transmission. Three methodological caveats have to be mentioned here.…”
mentioning
confidence: 81%
See 3 more Smart Citations
“…These results from experimentally manipulated honeybee colonies are in striking accordance with an independent study at the population level: studying honeybee and bumblebee populations in Varroa-free island refugia and in island and mainland sites positive for Varroa, Manley et al (2019) found that the presence of Varroa increased DWV-B prevalence and viral load both in Varroa's honeybee host as well as in wild bumblebees not infested by Varroa, but that DWV-A was virtually absent in the Varroa-free sites (Figure 1). Norton et al (2021) interpret these results as showing that DWV-B's recent increase in Europe and North America is not driven by selective pressure by the vector, which essentially suggests that DWV-B's spread is driven by higher reproductive capacity in honeybees irrespective of vector-borne transmission. Three methodological caveats have to be mentioned here.…”
mentioning
confidence: 81%
“…The honeybee Apis mellifera and its recently acquired ectoparasitic mite Varroa destructor present such a rare system, which Norton et al (2021) have used to test whether adaptation to vector-borne transmission can be a driver of the observed evolution of a novel epidemic bee virus variant (Figure 1). V. destructor is native to the East Asian honeybee A. cerana and jumped to the non-native Western honeybee A. mellifera in South-East Asia at the beginning of the 20th century (Anderson & Trueman, 2000).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, as V. destructor plays a major role in honeybee viral dynamics, beekeeping practices, such as treatments against V. destructor may affect viral evolution. One of the suggested mechanisms underlying the shift of DWV-A towards DWV-B is that DWV-B may be better adapted to vector-mediated transmission via V. destructor [ 78 , 95 , 96 ]. Furthermore, Norton et al [ 96 ] showed that the prevalence of DWV-A is highly dependent on the mite presence and density.…”
Section: Viruses and Their Variantsmentioning
confidence: 99%